Web-Based Petroleum Sales Accounting Information System - Fira Aulia; Ikbal Yasin; Yuri Rahmanto (Universitas Teknokrat Indonesia, 2022)
PT Radha Pratama Jaya is a business engaged in the sale of petroleum. Operations at PT Radha Pratama Jaya are carried out every day. With such an operating system, company management requires fast and accurate accounting information. So that the application of an accounting information system is needed by companies to get good information in order to facilitate the company's business activities. There are many sales transactions carried out in a day at PT Radha Pratama Jaya, and it causes employees to be unable to record transactions quickly. The use of computers that are still minimal because they still use a manual system makes the risk of misrepresentation very large. In addition, the archiving technique is not good, sales documents do not have duplicate documents so documents are easily lost because the storage is not good. The objective to be achieved in this study is to design a Web-Based Petroleum Sales Accounting Information System that is expected to be used by the Admin and sales department in assisting the Purchase and Sale of Petroleum at PT Radha Pratama Jaya. The method used in system development in this study is a prototype model because in the development of this system avoids time delays and costs far above what is budgeted to get a system that meets the needs of users. The result of this study is the processing of sales accounting information system data at PT Radha Pratama Jaya Bandar Lampung, currently, the data processing is still manual, resulting in the creation and search of purchase and sales reports needed by the leadership to be late when needed by the leadership. The Sales Accounting Information System at PT Radha Pratama Jaya Bandar Lampung can facilitate the search and update of data that will be used for the creation and search of Purchase and Sales reports needed by leaders